Implementasi Pemikiran Ki Hajar Dewantara pada Dunia Pendidikan: Literatur Review - Khoir, Mulyanto Abdullah; Widyaningsih, Erna; Muharromah, Fityatul (Lembaga Yasin AlSys, 2025)
Education plays a crucial role in shaping human thought and behavior, as well as determining the future of civilization. The Merdeka Curriculum emerges as an educational policy that grants freedom to schools, teachers, and students to innovate and learn independently. This study aims to analyze the relevance of the Merdeka Curriculum to Ki Hajar Dewantara's educational concept from a philosophical-pedagogical perspective. Through a literature review employing a hermeneutic-philosophical approach, it was found that the Merdeka Curriculum aligns with Ki Hajar Dewantara's views, emphasizing education as an effort to nurture students' natural potential. The concept of